Damping of thermo-mechanical stresses as a means of increasing the cyclic resistance of thermoelectric energy converters - Gorskyi, P.V. (Journal of Thermoelectricity, 2023)
Based on the combination of materials resistance methods with the Weibull approach, the requirements for stiffness coefficients of damping elements are determined, which can be used to reduce thermomechanical stresses in thermoelectric branches in order to increase the cyclic stability of thermoelectric energy converters. The Coffin-Manson power-law model for the dependence of the acceleration factor in the presence of cyclic temperature effects on the temperature drop is substantiated. The results of calculations are not only in qualitative, but also in satisfactory quantitative agreement with experimental data.